2003
DOI: 10.1038/sj.npp.1300156
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Testing Reveals a Dose-Dependent Difference in Methadone Maintained Vs Control Subjects

Abstract: Opiate addiction is associated with abnormal function of the stress-responsive hypothalamic-pituitary-adrenal (HPA) axis. In general, addiction and withdrawal are associated with abnormal HPA responsivity as demonstrated by baseline, dexamethasone, and metyrapone testing. Following stabilization in methadone maintenance treatment, normalization of HPA axis responsivity is observed. To further investigate HPA axis function associated with heroin addiction and its treatment, saline placebo and human corticotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 77 publications
1
31
0
2
Order By: Relevance
“…Previous studies provided evidence for dysregulation of the hypothalamic-pituitary-adrenal axis by chronic opiates (Kreek and Koob, 1998;Houshyar et al, 2001;Schluger et al, 2003). Given the role of the LC-NE system in stress and its regulation by opioids, this system presents an additional potential target through which chronic opiates could act to dysregulate the stress response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies provided evidence for dysregulation of the hypothalamic-pituitary-adrenal axis by chronic opiates (Kreek and Koob, 1998;Houshyar et al, 2001;Schluger et al, 2003). Given the role of the LC-NE system in stress and its regulation by opioids, this system presents an additional potential target through which chronic opiates could act to dysregulate the stress response.…”
Section: Introductionmentioning
confidence: 99%
“…One consequence that may contribute to drug-seeking behavior is dysregulation of the stress response (Kreek and Koob, 1998;Houshyar et al, 2001;Schluger et al, 2003). Dysregulation of the stress response may additionally predispose chronic opiate users to stress-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-related cues, stress or negative mood are associated with craving [2,3,4,5]. Several previous studies have shown the relevance of stress and hypothalamic-pituitary-adrenal (HPA) axis dysfunction in substance use disorders [6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Opioidinė priklausomybė yra susijusi ir su sutrikusia stresinio atsako funkcija pagumburio-hipofizės-antinksčių ašyje (toliau -PHA) [12]. Atliktoje klinikinėje studijoje, kurioje nuo opioidų priklausomiems, bet ilgą laiką nevartojusiems asmenims dirbtiniu būdu (naudojant metyraponą -medžiagą, laikinai blokuojančią kortizolio sintezę organizme) buvo sukelta farmakologinė gliukokortikoidų sintezės blokada, pasireiškė toks pat subjektyvus opioidų pavartojimo efektas kaip po tikros heroino dozės.…”
Section: Rezultataiunclassified